2023
DOI: 10.1615/critrevphysrehabilmed.2023045402
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Effect of Dance Therapy on Functioning in Children with Neuro-Motor Disorders

Abstract: Dance as movement therapy is known to improve balance, cardiorespiratory endurance, body composition, mood, and quality of life among healthy adults. Literature informing the effect of dance therapy on functional-outcome based on the International Classification of Function (ICF) model is lacking for children with neuro-motor impairment. Thus, the current study aimed to review the effect of various traditional dance forms on functioning based on the ICF model in children with neuro-motor disorders. The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Various dance forms, including creative dance, dance-based in somatic therapies, ballroom dance, hiphop, and classical ballet, have shown positive movement outcomes for persons with CP while increasing social participation. Previous studies have reported improved balance, gait, selective motor control, range of motion, rhythm production, and executive function (5)(6)(7)(8)(9). However, the neurophysiological mechanisms that underlie such improvements have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Various dance forms, including creative dance, dance-based in somatic therapies, ballroom dance, hiphop, and classical ballet, have shown positive movement outcomes for persons with CP while increasing social participation. Previous studies have reported improved balance, gait, selective motor control, range of motion, rhythm production, and executive function (5)(6)(7)(8)(9). However, the neurophysiological mechanisms that underlie such improvements have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%